Do impresso ao Google - Santos, Marígia Mádje Tertuliano dos (2015)
The ongoing transformations lead us to several questions. As stated by Beltran et al (2010), although studies on the relationship between science, art and technology have sought to understand and describe their nature, little has been done regarding the transmission of knowledge, as well as discussed about the media in which such knowledge are aired and its implications in the development of new scientific, technical and technological knowledge. This fact stresses the importance of seeking other sources for analysis in the history of science as expand the possibilities for a new look into the history of science and present it as an area of knowledge, with well-defined contours. Thus, one realizes that expands access to many works by digital means, but it is not clear that there is convergence between print and digital and that has solved the limitations in the production and distribution of knowledge, what justifies the proposal this work, which is to present the results of research conducted with students and teachers in a Private Institution of Higher Education, area of Exact Sciences, glimpsing the analysis of the use of Web 2.0 tools and services in the construction of knowledge